PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ISPRING SUITE 9 PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA KELAS X TITL DI SMK - Pinka Kezia; Hamonangan Tambunan (Universitas Negeri Medan, 2023)
Abstract The problem in this study is the lack of explanation of material in the form of animation, the use of technology in conveying information so that students do not understand and are interested in the material presented. Many students already have smartphones but only a small percentage use them for learning. Delivery of material in the form of textbooks, whiteboards and markers. The objectives of this study are (1) to determine the design process of developing Ispiring Suite 9 learning media in basic electrical and electronics subjects class X TITL, (2) to determine the feasibility of learning media designed so that this learning media is valid and can be used by students. The research model used in this study from Thiagarajan consists of define, design, development, and dissemination (4D). The subjects of this study were class X TITL2 students of SMKN 14 Medan, while the media assessment validators were UNIMED lecturers and homeroom teachers X TITL2 to assess the material and media. The results of this study show that interactive learning media based on Ispiring Suite 9 is classified as